Plasma miRNAs Effectively Distinguish Patients With Pancreatic Cancer From Controls: A Multicenter Study - Xu, Jianwei; Cao, Zhe; Liu, Wenjing; You, Lei; Zhou, Li; Wang, Chunyou; Lou, Wenhui; Sun, Bei; Miao, Yi; Liu, Xubao; Zhang, Taiping; Zhao, Yupei (Annals of surgery, 2016)
To identify plasma microRNA (miRNA) markers of pancreatic cancer (PC). Accurate pretreatment diagnosis of PC remains challenging, whether plasma miRNAs could be used as biomarkers in PC remains unknown. In this multiphase multicenter study, peripheral blood samples were obtained preoperatively in 3 phases: the discovery phase [7 patients with PC, 6 patients with chronic pancreatitis (CP), and 5 healthy volunteers (N)], the preliminary validation phase (29 patients with PC, 16 patients with CP, and 31 N), and the large sample validation phase (156 patients with PC, 65 N, 57 patients with CP, 27 patients with pancreatic neuroendocrine tumors, and 58 patients with other pancreatic tumors). The diagnostic values of the miRNAs were assessed and compared with cancer antigen 19-9 (CA19-9). The discovery phase demonstrated that 29 miRNAs were dysregulated in the patients with PC compared with the controls. In the preliminary validation phase, 13 miRNAs were shown to be dysregulated in the patients with PC and were selected for validation in a multicenter trial. MiR-486-5p exhibited diagnostic value in discriminating patients with PC from normal subjects or patients with CP, with area under the curve values of 0.861 and 0.707, respectively. MiR-938 exhibited diagnostic value in differentiating patients with PC from those with CP, pancreatic neuroendocrine tumors, and patients with other pancreatic tumors, with area under the curve values of 0.693, 0.660, and 0.618, respectively. In addition, we demonstrated that the value of miR-486-5p in discriminating patients with PC from normal subjects or patients with CP was comparable with that of CA19-9 (P = 0.602 and P = 0.230). This study identified several plasma miRNAs potentially suitable for distinguishing patients with PC from normal subjects or patients with other pancreatic tumors.